Clinical experience with using lacosamide for the treatment of epilepsy in a tertiary centre. (31st July 2012) - Kamel, J. T.; DeGruyter, M. A.; D'Souza, W. J.; Cook, M. J.
<x xml:space="preserve">Abstract</x> Objective Lacosamide is approved for the adjunctive treatment of partial‐onset seizures in adults. Phase II/III clinical trials suggest that it is a safe, effective and well‐tolerated medication. However, there is little post‐marketing information available about this medication. Methods We report our clinical experience from a tertiary referral epilepsy centre, which has been using lacosamide for the past 18 months, with 128 patients treated during this time. Results Fifty‐three patients (41%) achieved at least a 50% reduction in seizure frequency, with 14 patients (11%) achieving seizure freedom for a mean time of 35 weeks. This 50% responder rate matches, and the seizure free rate outperforms that seen in previous pooled trials. The efficacy of lacosamide did not vary with concurrent sodium channel blocking agent (SCB) use, and a statistically significant dose‐dependent response was not shown, which is in contrast to previous trials. Treatment emergent adverse effects (TEAEs) were noted in 52 patients (41%), with 24 patients (19%) discontinuing the medication. TEAEs were more frequent in patients on concurrent SCBs, affecting 51% vs. 28% of patients not on other SCBs. This increased risk of TEAEs from concurrent SCB use was of statistical significance (P = 0.01). The most frequently noted TEAEs from lacosamide were dizziness, sedation and diplopia, which all appeared to be dose‐related. Conclusion This post‐marketing analysis suggests that lacosamide in clinical practice at least mirrors, and possibly outperforms the results seen in previous phase II/III trials.